Post-translational governance of NF-κB in cancer immunity: mechanisms and therapeutic horizons - Hong, Yue; Fu, Ying; Long, Qian (Frontiers in Immunology, 2025)
Nuclear factor-κB (NF-κB) is a central transcriptional orchestrator of inflammation, immune modulation, and tumor progression. Beyond canonical signal transduction, the immunological functions of NF-κB are intricately governed by a spectrum of post-translational modifications (PTMs)—including phosphorylation, acetylation, ubiquitination, and methylation—that fine-tune its activation, nuclear translocation, DNA binding, and transcriptional specificity. In this Review, we explore how these context-dependent PTMs dynamically shape NF-κB’s role in cancer immunity: promoting macrophage polarization, controlling antigen presentation by dendritic cells, regulating T cell exhaustion, and sustaining immunosuppressive networks within the tumor microenvironment. We further delineate how PTM-mediated NF-κB signaling interfaces with immune checkpoint expression—particularly PD-L1 and IDO1—and fuels resistance to immunotherapies. Emerging pharmacological strategies targeting NF-κB-modifying enzymes or degradation via PROTACs hold promise to reprogram the immune landscape. By integrating mechanistic insight with translational potential, we position NF-κB’s post-translational regulation as a fertile axis for next-generation immunotherapeutic innovation.